Inequalities in caesarean section: influence of the type of maternity care and social class in an area with a national health system. Issue 3 (25th June 2008) - Salvador, J; Cano-Serral, G; Rodríguez-Sanz, M; Lladonosa, A; Borrell, C
Abstract : Objective: To analyse the impact of social class inequalities and type of maternity unit in the use of caesarean sections (CSs) among residents in an urban area of Southern Europe. Design: This was a cross-sectional study. The study population consisted of 2186 women resident in Barcelona city who gave birth to an infant without any birth defect during 1994–2003. The dependent variable was the type of delivery. Maternal age, social class and type of maternity unit (public or private) were independent variables. Maternal age-adjusted logistic regression models were used. Results: 30% of deliveries ended in CS; 70% of less privileged women delivered in public maternity units and 72% of more privileged women delivered in private centres. A relationship between CS and social class was observed (OR 1.4; 95% CI 1.1 to 1.7), but disappeared when the analysis was done separately for each stratum of type of maternity unit (both ORs 1.0). In contrast, a relationship between CS and type of maternity unit was found (OR 2.3; 95% CI 1.9 to 2.7), which persisted when the analysis was done separately for each stratum of social class. Conclusion: Although strongly related to higher social class, the main determinant of the high proportion of CSs was delivering in private maternity units.